The Measurement of Gains and Losses - Morgan, James N. (Quarterly Journal of Economics, 1948)
Consumer's surplus and public policy, 287. — Defining the concepts, 288. — Measures, 290. — Choice of concept depends on purpose for which it is desired, 295. — Graphic comparison, 295. — Application to a seller, 300. — Implications for compensation payments, 303. — Application to public policy, 307.